Low spikes and low harmonic distortion multilevel inverter for induction motor implementation - Aboadla, Ezzidin Hassan Elmabrouk; Aznan, Khairil Azhar; Tohtayong, Majdee; Khan, Sheroz; Hannan, Mohammad A.; Uddin, M. Nasir (IEEE, 2017)
Different Modulation techniques are suggested for use in electronic converters’ applications for getting minimized Total Harmonic Distortion (THD). One of such techniques a Selective Harmonics Elimination Pulse Width Modulation (SHE-PWM) scheme. Specific odd harmonics can be mitigated by operating the semiconductor switches in H-bridge inverters at optimized switching angles of the PWM signals. These switching angles are determined by calculating a set of nonlinear equations. Multilevel converters operated by PWM, suffer from the issue of harmonic spikes in the output voltage. In this paper, an improved scheme of SHE-PWM is proposed for multilevel converter to mitigate THD and supress the harmonic spikes of the system. To investigate and confirm the proposed technique, a five-level cascade multilevel inverter is simulated, and experimentally implemented. It is seen that the simulation results are verified experimentally by eliminating low- order harmoinics in getting a THD of 23.20% without using filter. The experimental results of the developed multilevel converer is validated with the simulation results under different performance conditions which show a complete agreement between them in terms of shapes and values.